The impact of emotional context on neural substrates of respiratory sensory gating - Chan, Pei-Ying S.; Chang, Wen-Pin; Cheng, Chia-Hsiung; Liu, Chia-Yih; von Leupoldt, Andreas; Hsu, Ai-Ling; Wu, Changwei W. (Frontiers in Neuroscience, 2022)
Psychological challenges have been found to impact respiratory symptom perception in healthy individuals as well as in patients with various neurological disorders. Human respiratory sensory gating is an objective measure to examine respiratory sensory information processing of repetitive respiratory mechanical stimuli in the central nervous system. With this electrophysiological method, patients with higher anxiety levels showed reduced respiratory sensory gating function in the cortex, and increased symptom perception. In addition, positive emotional contexts were found to increase the respiratory sensory gating function using RREPs. However, neural substrates related to emotional impacts on respiratory sensory gating remain still unclear. In the present study, we examined the emotion processing of respiratory sensory gating using functional magnetic resonance imaging. We hypothesized that positive compared with neutral stimuli would result in reduced brain activations in cortical areas with the paired occlusion paradigm. Thirty-five healthy adults participated in this event-designed fMRI experiment. Paired inspiratory occlusions (two transient occlusions with a 500ms inter-stimulus-interval are delivered during one inspiration) were provided using an external trigger outside of the scanner. At least 40 paired inspiratory occlusions were collected for each trial. The experiment contained three runs during which participants underwent 12 minutes for the paired inspiratory occlusion paradigm while watching a fixation cross (the control condition), neutral and positive emotional picture series. The order of emotional picture series was randomized across the participants. Our results revealed an overall trend of reduction of brain activity from the neutral (minus fixation) condition, to the pleasant (minus fixation) condition. For bilateral thalamus and primary visual cortices, there was no significant difference in neural activation between the two contrasts of pleasant (ContrastP-F) and neutral condition (ContrastN-F). The activation of the mid-cingulate and the orbitofrontal cortex was lower in ContrastP-F compared to ContrastN-F. In conclusion, our results suggest that emotional context, especially positive valence, modulates neural correlates in middle cingulate cortex and orbitofrontal cortex in terms of respiratory sensory gating. Future studies are recommended to test emotional impacts on respiratory sensations in patients with neurological disorders.